Moral Sensitivity, Ethical Experiences and Related Factors of Pediatric Nurses: A Cross- Sectional, Correlational Study - Tas Arslan, Fatma; Calpbinici, Pelin (Acta Bioethica, 2018)
The aim of this study is to determine the ethical experiences and the level of moral sensitivity and related factors of pediatric nurses working in hospital settings. Designed as descriptive and cross-sectional, the study was undertaken at three public hospitals in Konya and Ankara, Turkey and included the participation of a total of 200 pediatric nurses. The Moral Sensitivity Questionnaire (MSQ) was used for evaluation of the ethical sensitivities of the nurses. Of the 200 nurses, 46.5% had working experience of between 1–5 years, 58% were married, 18.6% had not undergone any ethics education, and 59.5% held a bachelor’s degree. A large majority (95%) of the pediatric nurses reported that they had encountered ethical problems. The mean moral sensitivity score of the nurses was 95.89±24.34, with higher scores in this area being observed in the nurses who were in the older age group and had worked longer than others (p<0.05). The mean moral sensitivity score of the nurses was determined to be at a medium level and was found to be influenced by the age group they were in and the length of time they had worked.